Ha-na-nim: A Korean Divine Name Taken Over for the Israelite God - Kee, Min Suc (The Bible translator, 2013)
It has been a successful venture for the Israelite god to take the name of the most respected god in Korea. Against the polytheistic background of the country, it seems that orthographical disputes over the name ha-na-nim have served to stir up the monotheistic zeal of Korean Protestants, giving support to their passionate mission of proclaiming the absolute oneness of God. As far as the orthography of the name is concerned, the logic of correct grammar has been set aside in the face of practicality and religious fervor around the name ha-na-nim.